Rol del Auditor de Sistemas en el modelo de Arquitectura Empresarial para entidades del Estado Colombiano (2021)
According to the regulatory framework defined by Department of Information Technologies and communications, the Colombian state entities must procure an efficient management to guarantee a good technology operation to all users, in all their daily activities related with the government services. All these, taken in consideration the governmental digital policy. Due to the above, to develop this article it had been identified and analyzed the components or domains of the model Enterprise Architecture. It must be applied in the Colombian state entities, in which, the control is an important factor to the model operation. As a result of this analysis, it was formulated a proposal that serves as a tool for the systems auditor in order to identify the model Enterprise Architecture components on its organizational level (strategic, tactic, operative), simulating risk assessment, the control evaluations, and the improve plans formulation, fulfilling like this, the role of the auditor.